(untitled) (Pedagogy of Higher and Secondary Education, 2014)
Lanova I. V. Value Ukrainian professional terminology in formuvanniprofesiynoyi speech competence future specialist. Highlights the objectives of higher school at present preparing future professionals to master the professional broadcasting – branch terminology. The different views on the concept of "time". A variety of exercises for effective learning terms and their active use in the Ukrainian professional speech.